PENGARUH PENGGUNAAN LKPD TERINTEGRASI MATERI ABRASI PANTAI TERHADAP KOMPETENSI PESERTA DIDIK DALAM MODEL INQUIRY LEARNING PADA MATERI GELOMBANG DI KELAS XI SMAN 2 PAINAN - Ayu Desra Andira; Ahmad Fauzi; Hamdi Rifai (Universitas Negeri Padang, 2017)
The low ability to understand the concept of learners to the material of physics causes the lack of motivation to learn learners so that the learning outcomes are low. The ability to understand the concepts of learners can be improved through one of the learning model is the inquiry learning model. For more contextual learning then integrated coastal abrasion problem. The purpose of this study was to investigate the differences, effects and contributions of integrated LKPD coastal abrasion materials to the competence of learners in the model of inquiry learning on wave materials in grade XI SMAN 2 Painan. This research type is quasi experiment with randomized control group design only design. The study population is all students of class XI MIPA SMAN 2 Painan registered in odd semester of academic year 2016/2017. Sampling of research using purposive sampling technique. The research data are data of students learning result of knowledge, attitude and skill competence and integrated LKPD value of coastal abrasion with post test instrument, attitude observation sheet, performance appraisal sheet, and LKPD assessment instrument. To know the difference of competence of learners is done two equality test equation, while to know influence and contribution of LKPD done regression and correlation test. The results showed that the experimental class knowledge aspect had mean of 82,71 and control class 77,21, experimental class attitude aspect 86,78 and control class 83,27, experimental class skill aspect 85,04 and control class 82,14. Through correlation test obtained value rhitung knowledge 0.80, attitude 0.61 and skill 0.69. LKPD's contribution to the knowledge aspect is very strong, with a contribution percentage of 64.27%. LKPD contribution to attitude aspect is strong, with contribution percentage equal to 37,71%. LKPD's contribution to the skills aspect is strong, with a contribution percentage of 48.1%